On the potential of drug repurposing in dysphagia treatment: New insights from a real-world pharmacovigilance study and a systematic review - Battini, Vera; Rocca, Sara; Guarnieri, Greta; Bombelli, Anna; Gringeri, Michele; Mosini, Giulia; Pozzi, Marco; Nobile, Maria; Radice, Sonia; Clementi, Emilio; Schindler, Antonio; Carnovale, Carla; et al. (Frontiers in Pharmacology, 2023)
Background Several drugs prevent the degradation of substance P, a neuropeptide enhancing swallow and cough reflexes. We aimed to explore the potential effects of drugs targeting substance P on dysphagia and aspiration pneumonia through a systematic review and a real-world data analysis. Material and Methods Five electronic databases were searched. Studies on adults at risk for dysphagia, treated with Dipeptidyl-Peptidase IV Inhibitors (DPP-4i), Adrenergic Beta-Antagonists (beta-blockers), Angiotensin-Converting Enzyme Inhibitors (ACEi), or Neprilysin inhibitors (ACNi), and reporting outcomes on dysphagia or aspiration pneumonia were included. A nested case/non-case study was performed on adverse events recorded in the FDA Adverse Event Reporting System (FAERS) on patients >64 years. Cases (dysphagia or aspiration pneumonia) were compared between patients only treated with Levodopa and patients who were concomitantly treated with the drugs of interest. Results Twenty studies were included in the review (17 on ACEi, 2 on beta-blockers, 1 on DPP-4i). Contrasting findings on the effects of ACEi were found, with a protective effect mainly reported by Asian studies on neurological patients. Beta-blockers were associated with a reduced dysphagia rate. The study on DPP-4i suggested no effect on dysphagia and an increased risk of aspiration pneumonia. The analysis from the FAERS showed a reduction of the risk for dysphagia/aspiration pneumonia with ACEi, beta-blockers, and DPP-4i. Conclusion Our study suggests the potential of repurposing ACEi and beta-blockers in neurological patients with dysphagia to improve swallowing function and reduce aspiration pneumonia risk. Future studies should confirm this result and analyze the role of substance P on the effect on dysphagia